Association between sperm mitochondrial ND2 gene variants and total fertilization failure. (4th July 2018) - Zhang, Jin-Lan; Mao, Gen-Hong; Huang, Xiao-Hui; Chang, Hong-Yang; Zheng, Yi; Cao, Xue
ABSTRACT: The objective of this study was to explore the association of sperm mitochondrial ND2 (MT-ND2) gene variants with total fertilization failure (TFF). A retrospective comparative study of 246 cases of fresh in vitro fertilization (IVF) cycles or half-intracytoplasmic sperm injection cycles in the Han Chinese population was performed from July 2011 to May 2017. A total of 59 cases undergoing TFF, and 187 control cases with normal fertilization (fertilization rates >50%) were included. The sperm mitochondrial genovariation was determined using nested sequencing. A total of 32 homoplasmic variants and 47 heteroplasmic variants of MT-ND2 gene were observed in this study. There were no significant differences in the frequencies of the 32 homoplasmic variants of MT-ND2 gene between the TFF and control groups. A total of 53 pair-wise comparisons were performed, and the general characteristics of the IVF failure and control subjects were adjusted in logistic models. Data suggested that there were no significant differences in the frequencies of point 4914, 5320, and 5426 heteroplasmic variants of MT-ND2 gene between the TFF and control groups. In addition, no significant difference was observed in the frequency of mtDNA haplogroup D or haplogroup G between the IVF failure group and the normal fertilization group. This study suggests that the MT-ND2 gene variants might not be associated with TFF. Abbreviations: ATP: adenosine triphosphate; dNTP: deoxy-ribonucleoside triphosphate; FADH2: flavin adenine dinucleotide; FDR: false discovery rate; FSH: follicle-stimulating hormone; IVF: in vitro fertilization; LH: luteinizing hormone; MTATP6: mitochondrially encoded ATP synthase 6; MTCYB: mitochondrially encoded cytochrome b; mtDNA: mitochondrial DNA; MT-ND2: mitochondrial ND2; NADH: nicotinamide adenine dinucleotide; ND2: NADH dehydrogenase subunit 2; OXPHOS: oxidative phosphorylation; PCR: single nucleotide polymorphisms; SNPs: single nucleotide polymorphisms; TFF: total fertilization failure